The Performative Aspects of Tamang Ritual in Chaitra Purne Jatra - Lama, Kumari (Tribhuvan University Journal, 2022)
Chaitra Purne Jatra, takes place in the month of Chaitra (March/April)when the Tamang people visit Namobuddha, Boudha and Swayambhu and performspecial rituals for the salvation of the departed soul. Against this backdrop,the paper explores examines and analyse the performative aspects of Chaitra PurneJatra taking Rabindra Tamang’s Timal Jatra (2054) as a primary text. Moreover, it concentrates on the dynamics of Tamang ritual. Performing specific cultural ritesin memory of their family members is a ritual process of the Tamang community. They begin the religious rites from Namobuddha and conclude in Swayambhu lighting the special light made up of astu powder, ghee and thread. At the end, people sing, dance and feast, which is reminiscent of the modern performances ontheatre that only highlight the subtle performative qualities of the jatra. To assess and scrutinize the performativity of the jatra, I have employed Richard Schechnerand Victor Turner’s concepts of ritual and performance.